A case of advanced ankylosing spondylitis complicated with cervical myelopathy due to ossification of yellow ligament in which bone histomorphometry demonstrated delayed calcification. (2nd July 2020) - Kondo, Naoki; Mizouchi, Tatsuki; Kubota, Kai; Endo, Naoto
Abstract: There is minimal information available about bone histomorphometric findings in patients with ankylosing spondylitis (AS). Herein, we report a case of advanced AS complicated with cervical myelopathy due to ossification of yellow ligament (OYL). A 37-year-old Japanese man who had been diagnosed with AS was administered adalimumab. Thirty-four months after adalimumab treatment, he reported upper extremity numbness, dexterity impairment and a spastic gait. Magnetic resonance imaging and computed tomography of the cervical spine revealed cervical cord compression at the C5/6 level due to OYL. After surgery including posterior spinal fusion and cervical cord decompression with iliac bone graft at C5 and C6 arches, these symptoms improved. Bone histomorphometry of his ilium revealed marked osteoid formation and reduced mineral apposition, suggesting a calcification disorder. In addition, 25-hydroxy vitamin D was abnormally low (<4 ng/mL), and at 148 pg/mL parathyroid hormone was higher than the reference value, indicating secondary hyperparathyroidism. This case warrants reporting because OYL was complicated with AS and bone histomorphometric findings in AS were evaluated.